Sorption of Lead Ions from Simulated Industrial Wastewater onto Jordanian Low-Grade Phosphate - Fahmi A. Abu Al-Rub (Adsorption Science & Technology)
The technical feasibility of using Jordanian low-grade phosphate (JLGP) for the removal of lead ions from aqueous solutions was investigated in this study. To simulate real industrial wastewaters, the effects of the presence of ethylenediaminetetraacetic acid (EDTA), citric acid, tartaric acid or sodium chloride on the adsorption of lead ions on JLGP were also investigated. The results of batch adsorption experiments demonstrated the high capability of JLGP for removing lead ions from aqueous solutions. The equilibrium data for the adsorption of lead ions onto JLGP could be fitted by the Langmuir, Freundlich, Temkin and Dubinin–Radushkevich (D–R) isotherm equations. The work presented showed that on using 1 mmol/l of an aqueous solution of any of Pb(II), Pb–NaCl, Pb–tartaric acid, Pb–EDTA or Pb–citric acid, the percentage removal of lead ions at equilibrium was in the order Pb(II) > Pb–NaCl > Pb– tartaric acid > Pb–citric acid > Pb–EDTA. Increasing the initial pH of the solution led to an enhancement in the sorption of lead ions and lead–ligand complexes onto JLGP. It was also found that increasing the concentration ratio of ligand to metal ion decreased the percentage removal of lead ions significantly. The sorption of lead ions from industrially simulated wastewater was found to follow pseudo-second-order kinetics.